Approaches and methods for evaluation of research organizations - Oanh, Nguyen Thi Thu; Braun, Michael (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper presents approaches and methods for evaluation of research organizations. This is a newly set-up concept to be applied in Vietnam because the methods developed in other countries do not match with science and technology (S&T) requirements and conditions in Vietnam which is being on a transfer process. The evaluation of research organizations is useful tools to support S&T management works since the outcomes of evaluation works would be indicators for management and support agencies to know results of activities of research organizations. At the same time, the outcomes of evaluation works would let research organizations themselves know the ways to improve efficiency of their own activities. Code: 14061601